Pre-contraction with the thromboxane-mimetic U46619 enhances P2X receptor-mediated contractions in isolated porcine splenic artery - Roberts, R. E. (Springer Netherlands, 2011)
We have previously demonstrated that the thromboxane-mimetic U46619 enhances α(2)-adrenoceptor-mediated contractions through increased activation of extracellular signal-regulated kinase (ERK). In this study, we determined whether U46619 also enhances P2X-mediated contractions through the same pathway. Segments of porcine splenic artery were mounted in isolated tissue baths. Tissues were pre-contracted with U46619 to 10–20% of the response to 60 mM KCl prior to addition of α,β-methylene ATP (P2X receptor agonist). The effect of inhibition of ERK activation with the mitogen-activated protein (MAP)/ERK kinase inhibitor PD98059 (50 μM), Rho kinase inhibition with Y27632 (10 μM), p38 MAP kinase with SB203580 (10 μM) or l-type calcium channels with nifedipine (1 μM) on both the direct and enhanced contractions was then determined. U46619 enhanced the contractions to α,β-methylene ATP. Although PD98059 inhibited the direct contractions to α,β-methylene ATP, it had no effect on the U46619-enhanced contractions. Similarly, Y27632 and SB203580 inhibited the direct contractions to α,β-methylene ATP, but had no effect on the enhanced contractions. Nifedipine inhibited the responses to α,β-methylene ATP in the absence and presence of U46619. This study demonstrates that pre-contraction with U46619 enhances P2X-mediated contractions in the porcine splenic artery through a mechanism independent of ERK, Rho kinase and p38 MAP kinase. Further studies are required to determine the exact mechanism involved.